Policy to replace electronic card into population digital in South Lampung Regency - Putri, Afifa Marsa; Syamsu, Syamsir; Triono, Agus (Goodwood Publishing, 2024)
Purpose: The aim of this research is to determine the need to implement a policy of replacing E-KTP with Digital Population Identity (IKD) in South Lampung Regency and to determine the implementation of a policy of replacing E-KTP with Digital Population Identity (IKD) in South Lampung Regency. Research methodology: This study employs a normative empirical method using a descriptive analysis approach. Secondary data were acquired through meticulous literature review and subjected to qualitative analysis. Rigorous literature selection ensured data validity. The outcomes of the analysis served as the basis for accurate conclusions within the research. Results: The research results show that changing KTP-e to IKD needs to be done because of the implementation of Permendagri No. 72 of 2022 concerning Standards and Specifications for Hardware, Software and Digital Identity Card Blanks. This was implemented because the e-KTP was no longer in line with the dynamics of the need for population administration services supported by a digital system. Limitations: The implementation of changing e-KTPs to IKDs in the South Lampung Regency has not been optimal, because the acquisition of IKD activations has only reached 14.04% of the number of existing villages and sub-districts. In practice, any service still requires a physical KTP. Contribution: This research explains that IKD is a solution to the problem of the scarcity of e-KTP blanks, which has always been an obstacle in implementing e-KTP because of the relatively high demand for recording and printing identity cards.